Sustainable Agriculture Practices: Economic, Ecological, and Social Approaches to Enhance Farmer Welfare and Environmental Sustainability - Kamakaula, Yohanes (West Science Nature and Technology, 2024)
This research aims to examine sustainable agricultural practices from economic, ecological, and social perspectives and how this approach can improve farmers' welfare and environmental sustainability. The research method used is a literature review, which collects and analyzes information from various sources such as scientific journals, books, and research reports. The results show that farm diversification, product value addition, and production efficiency are key strategies that can enhance farmers' economic welfare. From an ecological perspective, soil and water conservation practices, biodiversity management, and reducing chemical use are crucial for environmental sustainability. Socially, sustainable agriculture positively impacts farmers' welfare, community empowerment, and public health. Policy support, access to technology and markets, and comprehensive education and training are key factors in implementing sustainable agriculture. By integrating economic, ecological, and social perspectives, sustainable agriculture can be a holistic solution to modern agricultural challenges in Indonesia.